Nitrogen starvation for fuel production from Nannochloropsis: A trade-off between calorific lipid accumulation and energy loss for cell disruption - Mohammadhosein Rahimi; Paul A. Webley; Gregory J.O. Martin; Ronald Halim (Chemical Engineering Journal Advances, 2025)
Nitrogen starvation is widely used to boost lipid accumulation in algal biomass for biofuel production. However, its impact on cell wall architecture and the associated energy demands for biomass processing remain poorly understood. In particular, the extent of energy loss during mechanical cell disruption processes such as high-pressure homogenisation (HPH) has not been fully quantified, limiting our understanding of the overall energy efficiency of this approach. This study examines how nitrogen starvation alters lipid content and cell wall structure in Nannochloropsis, and the effect of these changes on downstream biodiesel processing. Under nitrogen deprivation, cells redirected photosynthetically fixed carbon toward triacylglycerol and cellulose synthesis, resulting in a concurrent 1.4-fold increase in lipid content and a 1.7-fold thickening of the cell wall. De novo synthesis of C16:0 and C16:1 fatty acids led to a 1.4-fold increase in biomass calorific value. However, thickened walls reduced HPH cell rupture efficiency from 33.7 % to 22.9 %.Although nitrogen starvation raised the energy required for cell disruption by 22.6 %, this was outweighed by an 80.6 % gain in stored lipid energy, reducing the proportion of HPH energy relative to lipid energy from 48.0 % to 20.0 %. These findings highlight nitrogen starvation as a promising strategy to enhance overall energy balance of downstream processing. However, HPH was still inefficient, with up to 65.5 % of input energy lost as heat, underscoring the need for an integrated heat recovery systems to achieve scalability.